(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2025)
An incubation study was conducted to investigate the effects of four organic amendments (e.g., banana peel, BP; eggshell, ES; tea waste, TW; and vermicompost, VC) on chemical properties of an acidic sandy loam soil. Three incubation periods viz. 38, 120, and 240 days (d) and two rates, e.g., 4% and 8% (w/w) of amendments with three replicates were considered. Amendments and incubation time had significant impacts on soil chemical properties. It was revealed that soil pH, EC, OC, TN, extractable P, K, Ca, Mg, Fe, Cu, Mn, and Zn were increased in most of the amended soils. However, ES had no impact on TN and K. Moreover, it decreased micro-nutrients concentrations. BP and TW had no impact on Ca and Cu, respectively. Soil pH raised (> 8.0) in ES and BP amended soils. Highest OC was recorded in VC and TW amended soils. Highest EC, P, Mg, and micronutrients, except Fe, was recorded in VC amended soils. Both K and Fe was highest in BP; and Ca was highest in ES amended soils. Overall, soil pH, OC, TN, extractable K, Mg, Cu, and Mn significantly reduced with incubation time. In contrast, soil EC, extractable P, Fe, and Zn increased. J. Asiat. Soc. Bangladesh, Sci. 51(1): 73-86, June 2025